Protection of Musical Work Copyright on Digital Platforms: A Comparative Study of Indonesian and United States Law - Citra Bintang Maranatha Manurung; Ridha Wahyuni (Jurnal Daulat Hukum, 2025)
The development of digital technology has changed the way people produce, distribute, and use musical works. However, this progress has also increased the potential for copyright infringement, especially on User-Generated Content (UGC) platforms such as YouTube, TikTok, and Instagram. In this context, Law No. 28 of 2014 on Copyright protects the moral and economic rights of creators, but it lacks the technical rules required to address violations in the digital environment. The absence of a notice-and-takedown mechanism, safe harbor provisions, and an obligation to use automated detection technology indicates that Indonesia’s legal framework remains inadequate to address large-scale infringements. In contrast, the United States, through the DMCA 1998, provides detailed regulation of notice-and-takedown procedures, safe harbor requirements, and platform obligations in dealing with repeat infringers. Through a normative, juridical, and comparative legal approach, this study analyzed differences between the Indonesian and U.S. systems and identified gaps that weakened copyright enforcement in Indonesia. The findings show that Indonesia requires more specific technical regulations to support adequate protection on digital platforms. Therefore, this research proposes an ideal protection model comprising four integrated components: clear, binding technical regulations, automated detection technology, a centralized copyright database, and a fair monetization mechanism. The integration of these elements is expected to strengthen copyright enforcement, enhance legal certainty, and support a more accountable and sustainable digital ecosystem.